Social protection schemes in rural Rwanda: A panacea for household energy burdens? - Khundi-Mkomba, Fydess; Saha, Akshay Kumar; Wali, Umaru Garba (Energy for sustainable development, 2023)
The role of social protection programs in low-income countries is increasingly becoming a subject of interest on the development agenda in the public discourse. The literature reveals a diversity of findings about the role of social protection on household development outcomes. There is little documentation regarding how social protection schemes affect household energy burdens in rural areas, especially in Sub-Saharan Africa. Rwanda is one of the African countries that have taken deliberate steps to institutionalize the provision of social protection schemes to its citizenry. Therefore, this paper examined how accessibility to different social protection schemes affected household energy burdens in rural Rwanda using nationally representative household-level microdata (EICV5). Results from the Lewbel Instrumental Variable Estimator, nearest neighbor matching, and Inverse Probability Weighted Regression Adjustment showed that Vision 2020 Umurenge and Girinka social protection schemes significantly negatively affected household energy cost burdens. These study findings suggest that social protection schemes may require other efforts or policy instruments that might encourage use of modern energy services to address energy affordability barriers in rural areas. •The study found that Vision 2020 Umurenge and Girinka social protection schemes significantly negatively affected household energy cost burdens in rural Rwanda.•These study findings suggest that social protection schemes may require other efforts or policy instruments to address energy affordability barriers in rural areas.•The study recommends that Rwandan government may consider engaging energy policy entrepreneurs at all levels as focal points in the energy policy process.